Outcome of intrauterine adhesion management at a Nigerian tertiary hospital: a five-year review - Opadiran, R. O.; Isah, A. D.; Agida, E. T.; Adewole, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrauterine adhesion is a cause of menstrual abnormalities and infertility, which are leading complaints in gynaecological practice in Nigeria. Determining the aetiology and management option would help reduce this problem. The objective of this study was to determine the aetiology, mode of presentation, management option and outcome of intrauterine adhesions Methods: A retrospective analysis of intrauterine adhesions at the University of Abuja Teaching Hospital over a five-year period from 2012 to 2016 was carried out. The case notes of the patients were retrieved from the records department and information extracted from these case notes using a questionnaire included the age, level of education, marital status, parity, complaints, predisposing factors, method of diagnosis, treatment method and outcome. Additional information was obtained from the theatre registered. The least follow up period was one year. Results: There were 82 patients diagnosed with Intrauterine Adhesion over the study period giving an incidence of 1.6%. Fifty-nine case notes were available for analysis. The case note retrieval rate was 72%. Majority of the patients were between the age range of 30-34 years (21, 35.6%). Those with tertiary level of education constituted the majority (34, 57%). Nullipara constituted 54.2% (32) of the total population. Menstrual abnormalities were the most common complaint with 93.2% and this includes those with menstrual abnormalities and other complaints. The commonest predisposing factor identified was a history of dilatation and curettage or uterine evacuation (28, 47.5%). Majority of the patients had partial intrauterine adhesions (51, 86.4%). All patients were treated with adhesiolysis, Foleys catheter insertion and hormonal therapy for 3 cycles. There was not statistical significance between those who had blind adhesiolysis and hysteroscopic adhesiolysis in terms of outcome. Restoration of menstrual flow was in 25, (42.4%) while 3, (5.1%) had miscarriges and an equal no of patients had term delivery. Conclusions: Dilatation and curettage is still a major predisposing factor in the development of intrauterine Adhesions. Blind adhesiolysis still has its place in the management of intrauterine adhesion in developing countries.